Effect of aging on microstructure and mechanical properties of cobalt free 18%Ni (250 grade) maraging steel - Sinha P.P.; Tharian K.T.; Sreekumar K.; Nagarajan K.V.; Sarma D.S. (My University, 2025)
The influence of aging on the microstructure, tensile properties, fracture toughness, and fractographic features of a cobalt free 18%Ni 250 grade maraging steel has been investigated. This steel, designated as T250 steel, with 17.1%Ni, 2.25%Mo, and 1.39%Ti as the main alloying elements, contains no cobalt and less molybdenum than the widely used 18Ni-8Co-5Mo type 250 maraging steel (M250). The present investigation shows that tensile properties as well as plane strain fracture toughness values comparable with those of M250 can be obtained in the T250 steel with marginal change in aging cycle. The Ni3Ti phase precipitating in the present steel has been found to have excellent resistance to coarsening at the normal aging temperatures. The condition for maximum yield and tensile strengths is also the one that gives peak values of toughness. While a low value of toughness in the underaged condition is attributed to the planar slip mode of deformation, the formation of reverted austenite and coarsening of precipitates were responsible for the poor toughness in the averaged condition. The strengthening in the present steel obeys the modified Orowan equation. © 1998 The Institute of Materials.